The Influence of a Community Science Technology Learning Model Based on a Scientific Approach to Improve Science Learning Outcomes - Marzuki, Ahmad Dedi; Usman, Usman (Jurnal Pijar Mipa, 2024)
The science and technology model is learning to teach science and technology in the context of experience and everyday life, focusing on societal issues, whether local, regional, national, or global, with science and technology components. Meanwhile, the scientific approach is an approach to learning science process skills. It uses a scientific approach where students are directed and guided in observing, asking, trying, reasoning, and building networks to disseminate the learning results obtained. Learning outcomes are a path to mastering knowledge or skills in a subject, usually indicated by test scores or numbers given by the teacher. Learning outcomes are obtained from learning to master knowledge, usually developed and shown by numbers. This research aims to determine whether implementing a science and technology learning model based on a scientific approach affects the science learning outcomes of grade IV students at SDN Pemongkong. Researchers are implementing technology in science learning at SDN 1 Pemongkong. Still, many obstacles exist, such as internet signals and technological stupors; only some have a laptop or cellphone. Therefore, the idea that emerged in this research was the use of technology that can be accessed by all students, namely the community science technology model based on a scientific approach, which is expected to improve student learning outcomes. The method used in this research is experimentation. This type of experimental research uses Quasi-Experimental Design or quasi-experiments. The experimental plan used in this research is a Nonequivalent Control Group Design. Hypothesis testing is carried out using uji t (independent samples test). Comparison of the average learning outcomes of the experimental class and the control class for the two classes experienced an increase compared to before learning; namely, the average value of the control class at the pretest 54.82 and increased to 73.10 after learning, while the average value of the experimental class is at posttest 58.07 and rose to 74.42 on posttest. The average learning outcomes are similar between the control class and the class experiment. However, the average learning outcomes of the experimental class are still higher than those of the control class. The class that was taught used the community science and technology learning model. Namely, two students got a score of 90 in the control class, and in the conventional class, only one got a 90. By hypothesis testing, face H0 accepted that the scientific approach-based community science and technology learning model influences the learning outcomes of class IV students at SDN 1 Pemongkong. In this case, it can be interpreted that the community science and technology learning model positively impacts student learning outcomes.